Silvia y Bruno - Carroll, Lewis, 1832-1898; Alonso Valle, Axel; Carroll, Lewis, 1832-1898. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2013)
Two fairy children meet adventure in such places as Dogland, Outland, and Elfland.
Online resource; title from ePub title page (Digitalia, viewed January 9, 2017)
Keywords: Fairies -- Fiction; London (England) -- History -- 1800-1950 -- Fiction; Fantasy fiction; Fiction; Electronic books